Obesity and sarcopenic obesity characterized by low-grade inflammation are associated with increased risk for major depression in women - Pasco, Julie A.; Berk, Michael; Penninx, Brenda; Hyde, Natalie K.; Holloway-Kew, Kara L.; West, Emma C.; Kotowicz, Mark A.; Anderson, Kara B.; O’Neil, Adrienne; Rufus-Membere, Pamela G.; Williams, Lana J. (Frontiers in Nutrition, 2023)
Background: We aimed to determine women’s risk of major depressive disorder (MDD) in relation to obesity phenotypes characterised by levels of circulating high-sensitivity C-reactive protein (hsCRP). Methods: This population-based retrospective cohort study comprised 808 women (ages 20-84y) recruited 1994-1997 and followed for a median 16.1y (IQR 11.9-16.8). At baseline, body fat and lean tissue mass were measured by whole body dual-energy x-ray absorptiometry (DXA). Obesity was identified as high fat mass index (>12.9kg/m2), body fat percentage (≥35%) and body mass index (≥30kg/m2); sarcopenic obesity referred to a high ratio fat mass/fat-free mass (≥0.80). Systemic inflammation was operationalised as serum hsCRP concentration in the upper tertile (>2.99mg/L). Obesity phenotypes were: nonobese+lowCRP, nonobese+highCRP, obese+lowCRP, and obese+highCRP. During follow-up, the Structured Clinical Interview for DSM-IV-TR (SCID-I/NP) was used to identify lifetime history of MDD and age of onset. Poisson regression models were used to estimate the MDD rate for each obesity phenotype during follow-up. Demographic, health and lifestyle factors were tested as potential confounders. Results: During 11,869 p-y of follow-up, 161 (19.9%) women experienced an MDD episode. For obesity phenotypes based on fat mass index, models adjusted for baseline age and prior MDD, and nonobese+lowCRP as reference, RR for nonobese+highCRP was 1.21 (95%CI 0.80, 1.82), obese+lowCRP 1.46 (0.86, 2.47) and obese+highCRP 1.56 (1.03, 2.37). Patterns were similar for obesity by body fat percentage, body mass index and sarcopenic obesity. Conclusion: Consistently across different obesity definitions, this longitudinal study reports that women with both obesity and systemic inflammation are at increased risk of subsequent MDD. Future research should examine whether tackling this metabolically unhealthy obesity type – through, for example, lifestyle or medication approaches – can reduce depression risk.